The Effects of Short Term Intracanal Medicaments on the Fracture Resistance of Root in Pulp Revitalization Procedure - Lima Neto, JosÃ© Cordeiro; Alves de Souza Barbosa, Monnice Helena; Dantas Batista, AndrÃ© Ulisses; Coelho Sinhoreti, Mario Alexandre; Rocha Lima, Thiago Farias (Iranian Endodontic Journal, 2019)
Introduction: The objective of this study was to evaluate the effects of short term intracanal medicaments on the fracture resistance of root in simulated necrotic immature teeth in pulp revitalization procedure. Methods and Materials: Bovine teeth (n=180) were selected, sectioned coronally and apically and then, internally fragilized. Intracanal medicament groups were arranged as follows: “Triple Antibiotic Paste” (TAP) group (n=60), “Calcium Hydroxide” (CH) group (n=60) and the control group (n=60). No medication was used in the control group. Fracture resistance tests were performed after 7, 14, and 21 days. At allocated intervals, 20 teeth from each group had fractured. The Kruskal-Wallis and Mann-Whitney tests were performed to verify the effects of the employed medicaments at each time point. Friedman test and Wilcoxon signed-rank test were also performed to verify the association between time and fracture resistance. The level of significance was set at 0.05. Results: After 7 days, there was no statistical difference between groups (P=0.376). Intragroup analysis revealed that, after 21 days, the TAP group (P=0.015) and the CH group (P=0.006) presented a statically significant reduction in fracture resistance comparison with 7 days. Statistical difference was not verified for the control group after 7, 14 and 21 days (P=0.25). There was no statistical difference between CH group and the control group after 7, 14 and 21 days (P>0.05). The reduction was significant for TAP after 14 and 21 days (P=0.018, P=0.033 Respectively). Conclusions: This in vitro study showed that the duration at which TAP and CH remained in the root canal influenced the fracture resistance of bovine teeth with simulated incomplete root formation. Keywords: Calcium Hydroxide; Endodontics; Regeneration; Triple Antibiotic Paste